The International Finance Corporation : origin, operations, and evaluation - Baker, James Calvin (New York : Praeger, 1968)
This book seek to examine the International Finance Corporation, the origin, general and specific operations, problems, and value that can be studied within the framework of the dynamism of today's changing patterns in world economic assistance.
Includes index
Bibliography: p. 253-262.
usc 20/07/18
Loans
Keywords: Finance; International Finance Corporation; Developing countries